Comparison of non‐volatile and volatile flavor compounds in six Pleurotus mushrooms. (16th October 2018) - Yin, Chaomin; Fan, Xiuzhi; Fan, Zhe; Shi, Defang; Yao, Fen; Gao, Hong
Abstract: BACKGROUND: Non‐volatile and volatile flavor compounds of six Pleurotus mushrooms including Pleurotus citrinopileatus, P. cornucopiae, P. djamor, P. floridanus, P. ostreatus and P. sapidus were studied. RESULTS: The content of total free amino acids ranged from 21.80 to 40.60 g kg −1 and the content of monosodium glutamate (MSG)‐like amino acids ranged from 3.10 to 8.64 g kg −1 . The content of total 5′‐nucleotides ranged from 4.16 to 8.80 g kg −1 while the content of flavor 5′‐nucleotides ranged from 2.00 to 4.51 g kg −1 . Sixty‐three volatile compounds were identified in six Pleurotus mushrooms, including 17 aldehydes, 10 ketones, 14 alcohols, 2 ethers, 5 acids, 5 hydrocarbons, 10 heterocyclic and aromatic compounds. 1‐Octen‐3‐one and 1‐octen‐3‐ol were the key odor compounds in P. citrinopileatus, P. djamor, P. ostreatus, P. floridanus and P. sapidus, while 1‐octen‐3‐one, 1‐octen‐3‐ol and 2‐octenal were the key odor compounds in P. cornucopiae . CONCLUSION: Pleurotus citrinopileatus had highest content of total free amino acids (40.60 g kg −1 ), total 5′‐nucleotides (8.80 g kg −1 ) and flavor 5′‐nucleotides (4.51 g kg −1 ) than other Pleurotus mushrooms. Moreover, eight‐carbon compounds were the most abundant compounds in six Pleurotus mushrooms. Our study should be helpful in promoting the cultivation and consumption of these Pleurotus mushrooms. © 2018 Society of Chemical Industry